Port Fairy Folk Festival Music ([Australia] : Geelong Folk Music Club, 1985)
Features a reproduction of an engraving of ships in harbour and a row boat. Printed in red and blue ink on textured paper.
"March 8-11, 1985".
Catalogue record generated as part of a batch load.
Also available online
Keywords: Folk festivals -- Australia -- Posters; Folk festivals -- Victoria -- Port Fairy -- Posters